Businesses and the challenge to overcome the crisis originated by COVID-19 - Esteban Espinoza, David (2022)
This situation affected business organizations in various ways, especially those that were forced to close for a determined or undetermined period of time. Companies have had to adapt to the new normal situation, making changes in their businesses in parallel with the implementation of health and social distancing protocols. In this way, companies adapted their business strategies to a new situation and reinvented their value propositions. In order to face this crisis, the use of technology has been essential, which has reduced costs for companies. At the same time, the governments strategies to reactivate the economy have been of great help to be able to boost business, thus being essential to keep the operation and operability of companies. (Suarez, 2020)